Role of glucocorticoid receptor expression in Chronic Chagas Cardiomyopathy: implications for inflammation and cardiac hypertrophy - González, Florencia B.; Pacini, Antonella; Castro, Araceli; Lioi, Susana; Villar, Silvina R.; D’Attilio, Luciano; Leiva, Rodolfo D.; Favaloro, Liliana; Bottasso, Oscar A.; Vigliano, Carlos A.; Pérez, Ana Rosa (Frontiers in Endocrinology, 2025)
IntroductionChronic Chagasic Cardiomyopathy (CCC) has an infectious and inflammatory nature. Recent data also suggest an association with altered regulation of glucocorticoid (GC)-mediated circuits failing to control systemic inflammation. However, the involvement of glucocorticoid receptors (GR) and their isoforms have been unexplored.Materials and methodsThe expression of GR-α/β isoforms, 11β-hydroxysteroid dehydrogenase type-1 (11β-HSD1), inflammatory cytokines, and the GC-regulated gene tristetraprolin (TTP) in peripheral blood mononuclear cells (PBMCs) as well as GR immunoreactivity in the myocardium from CCC individuals were evaluated by qPCR and immunohistochemistry respectively. Heart control samples with no evidence of structural heart disease and from ischemic cardiomyopathy patients were included. The presence of inflammatory infiltrates and fibrosis were also recorded.ResultsGR-α was expressed similarly in the PBMCs from Co and CCC individuals, but 11β-HSD1 expression was increased only in CCC, conjointly with enhanced ratios of IL-6/TTP and IFN-γ/TTP. In the inflamed myocardium from CCC patients, positive GR expression correlated with the intensity of the inflammatory infiltrate and cardiac hypertrophy.ConclusionThe infectious and inflammatory nature of CCC pathology seems strongly connected with the expression of GR in cardiac tissue samples, providing a stimulating background for further studies addressed to elucidate the influence of GR expression and function on CCC pathophysiology and cardiomyocyte hypertrophy.